Progressive symptoms and signs following institution of highly active antiretroviral therapy and subsequent antituberculosis therapy: immune reconstitution syndrome or infection?. Issue 2 (30th March 2006) - Miller, R F; Shahmanesh, M; Talbot, M D; Wiselka, M J; Shaw, P J; Bacon, C; Robertson, C M
Abstract : A 36 year old man presented with weight loss, cough, fever, and exertional dyspnoea shortly after a diagnosis of HIV infection. Symptoms and initial radiological abnormalities worsened after highly active antiretroviral therapy was started. An eventual diagnosis was established but multiple problems occurred throughout the treatment period. Differentiation between immune reconstitution inflammatory syndrome and an infective cause was problematic.